APOE Christchurch enhances a disease-associated microglial response to plaque but suppresses response to tau pathology - Kristine M. Tran; Nellie E. Kwang; Claire A. Butler; Angela Gomez-Arboledas; Shimako Kawauchi; Cassandra Mar; Donna Chao; Rocio A. Barahona; Celia Da Cunha; Kate I. Tsourmas; Zechuan Shi; Shuling Wang; et al. (Molecular Neurodegeneration)
Abstract Background Apolipoprotein E ε4 (APOE4) is the strongest genetic risk factor for late-onset Alzheimer’s disease (LOAD). A recent case report identified a rare variant in APOE, APOE3-R136S (Christchurch), proposed to confer resistance to autosomal dominant Alzheimer’s Disease (AD). However, it remains unclear whether and how this variant exerts its protective effects. Methods We introduced the R136S variant into mouse Apoe (ApoeCh) and investigated its effect on the development of AD-related pathology using the 5xFAD model of amyloidosis and the PS19 model of tauopathy. We used immunohistochemical and biochemical analysis along with single-cell spatial omics and bulk proteomics to explore the impact of the ApoeCh variant on AD pathological development and the brain’s response to plaques and tau. Results In 5xFAD mice, ApoeCh enhances a Disease-Associated Microglia (DAM) phenotype in microglia surrounding plaques, and reduces plaque load, dystrophic neurites, and plasma neurofilament light chain. By contrast, in PS19 mice, ApoeCh suppresses the microglial and astrocytic responses to tau-laden neurons and does not reduce tau accumulation or phosphorylation, but partially rescues tau-induced synaptic and myelin loss. We compared how microglia responses differ between the two mouse models to elucidate the distinct DAM signatures induced by ApoeCh. We identified upregulation of antigen presentation-related genes in the DAM response in a PS19 compared to a 5xFAD background, suggesting a differential response to amyloid versus tau pathology that is modulated by the presence of ApoeCh. Bulk proteomics show upregulated mitochondrial protein abundance with ApoeCh in 5xFAD mice, but reductions in mitochondrial and translation associated proteins in PS19 mice. Conclusions These findings highlight the ability of the ApoeCh variant to modulate microglial responses based on the type of pathology, enhancing DAM reactivity in amyloid models and dampening neuroinflammation to promote protection in tau models. This suggests that the Christchurch variant's protective effects likely involve multiple mechanisms, including changes in receptor binding and microglial programming. Graphical Abstract